A comparative study on carbon stock in Sal (Shorea robusta) forest in two different ecological regions of Nepal - Pandey, H. P.; Bhusal, M. (Banko Janakari, 2016)
Estimation of total biomass and carbon sequestration in any forest is crucial as it gives ecological and economic benefits through various environmental services. With an aim to quantify the carbon stock densities in the two different ecological regions–the Hills and the Terai, two Community Forests (CFs) having the dominance of Shorea robusta were selected from Gorkha (in the Hills) and Chitwan (in the Terai) districts for the purpose of the study. Systematic random sampling with 1% sampling intensity was used to collect necessary data. The total carbon stock in the CFs of the Hills and the Terai were found to be 234.54 t ha-1 and 479.29 t ha-1, respectively. The biomass carbon stock density in the CF of the Terai was found to be higher (384.20 t ha-1) than the one in the Hills (123.15 t ha-1). Carbon densities of different carbon pools such as tree; sapling; leaf litter, grass and herbs were significantly higher (P<0.05) in the Terai than in the Hill forest whereas dead wood and stumps and the soil organic carbon density were found to be not significantly different in these regions. Similarly, the highest amount of soil organic carbon (SOC) was found in the uppermost soil horizon in the forests of both the regions. These results revealed that the biomass carbon stock density was higher in the Terai S. robusta forest than in the Hill S. robusta forest. However, the SOC obtained was in inverse relation to that of the biomass carbon stock in both the ecological regions. It would not be biased if different ecological regions with similar forest types are intervened with different management strategies for having more carbon stocks and for the conservation of biodiversity in the days to come. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page: 24-31, 2016